Analysis Of Determinants Of Smoking Behavior - Apir; Widyowati, Agustin (Journal of Global Research in Public Health, 2024)
Nearly 9 out of 10 adults first smoke at age 18. 1600 teenagers smoke for the first time every day in the U.S. (CDC, 2022) Unprevented smoking behavior will certainly have an impact on health, economy, stunting, and even the environment. The study aims to identify determinants of smoking behavior in Lowokwaru District, Malang City. The research method is a quantitative method with a cross-sectional study design carried out in November 2024. Data were collected through the Assessment and Questionnaire website with a sample of 338 people. Data analysis using univariate tests. The results of the study stated that the majority of respondents were aged <45 years at 93.6%, then the majority were male at 94.4%. then the majority of their marital status was married at 59.2%, then the majority of BMI was obese at 59.8%, then the majority of blood pressure was normal at 95.6%, and the majority of triglyceride levels were 55%. It is expected that the government through the Ministry of Finance can consistently increase cigarette prices and immediately make a policy prohibiting retail cigarette sales. In addition, health agencies can make health promotion efforts for adolescents and conduct comprehensive smoke-free area supervision in schools.